Urea-formaldehyde resin doped bamboo parenchyma cell porous carbon electrode material and preparation method thereof
By mixing bamboo thin-walled cells with urea-formaldehyde resin powder, carbonizing and activation, a porous carbon electrode material of urea-formaldehyde resin-doped bamboo thin-walled cells was prepared, which solved the problem of specific capacitance limitation in existing bamboo carbon materials in energy storage applications, and achieved electrode materials with large specific surface area and high tap density, which were suitable for high-performance supercapacitors.
Patent Information
- Application Number
- CN202411952487.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
It is difficult for existing bamboo carbon materials to break through the specific capacitance limit in energy storage applications, and the ash content and low tap density are difficult to meet the specific capacity requirements of high-performance supercapacitors.
By mixing bamboo thin-walled cells with urea-formaldehyde resin powder, carbonizing and activation, a urea-formaldehyde resin-doped bamboo thin-walled cell porous carbon electrode material was prepared, and a porous structure was formed during the pyrolysis process using urea-formaldehyde resin to enhance the specific surface area and tap density of the material.
The prepared electrode material has a large specific surface area, high nitrogen doping amount, and an improved tap density, which can significantly improve the specific capacity performance of supercapacitors and is suitable for the positive electrode material of zinc ion hybrid capacitors.
Smart Images

Figure CN119637873A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical energy storage materials, and particularly relates to a urea-formaldehyde resin-doped bamboo thin-wall cell porous carbon electrode material and a preparation method thereof. Background Art
[0002] Bamboo is a widely distributed and highly potential biomass resource in my country, with special advantages such as fast growth rate, high fiber strength and large deflection. The current bamboo forest area in my country is 7.5627 million hm2. 2 Bamboo processing industry has become one of the key industries in forestry development. At present, my country consumes about 250 million tons of bamboo materials annually, and the bamboo residues generated have exceeded 130 million tons. Bamboo fiber and bamboo parenchyma cells are the main tissues, accounting for about 40% and 52% of the volume of bamboo tissues. Bamboo parenchyma cells have a loose structure. Therefore, in bamboo processing, bamboo parenchyma cells are the main component of bamboo processing residues, but they are often overlooked in the research and high value-added utilization of bamboo residues. Bamboo fiber and bamboo parenchyma cells are completely different in microstructure. Studies have shown that the natural pore structure of bamboo parenchyma cells makes it easier to prepare activated carbon with rich pore structure, which has good application prospects in supercapacitors and adsorption fields.
[0003] Bamboo parenchyma cells have multi-walled, porous and cavity structures. During the activation process, the pits and multi-layer structures on the cell walls help the activator to be completely impregnated and etched to build a developed pore structure. However, in energy storage applications, single bamboo carbon materials only rely on the internal pores to absorb / desorb ions in the electrolyte to achieve energy storage and release. This energy storage mechanism makes it difficult for pure bamboo carbon materials to break through the limitations of their own specific capacitance and meet the specific capacity requirements of high-performance supercapacitors. In addition, the rich silicon and cavity structure in the parenchyma cells make the carbon materials prepared therefrom have problems of high ash content and low tap density. Therefore, composite modification treatment is a prerequisite for bamboo carbon materials to achieve excellent electrochemical properties. Xu believes that using the cavity structure of thin-walled cells to composite or load other substances can achieve good synergistic effects, among which nitrogen doping is a common way to modify and enhance porous carbon (Z. Xu, X. Zhang, K. Li, et al., 2020. Green Synthesis of Fe-Decorated Carbon Sphere / Nanosheet Derived from Bamboo for High-Performance Supercapacitor Application[J]. Energy & Fuels. 351, 827-838.). Urea-formaldehyde resin is a thermosetting amino resin with simple composition, extremely low ash content and high nitrogen content. Urea-formaldehyde resin has extremely poor thermal stability and is easily decomposed and expanded to form a porous structure when heated. With this characteristic, urea-formaldehyde resin is composited with thin-walled cells, which can fill the urea-formaldehyde resin into the cavity structure of thin-walled cells during the pyrolysis process, thereby increasing the tap density of porous carbon materials, and introducing more electrochemical active sites through heteroatom doping to improve the capacity performance of porous carbon. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material, which has a large specific surface area and a high nitrogen doping amount; another technical problem solved by the present invention is to provide a preparation method of a urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material, and the production conditions of the method are simple and controllable; another technical problem solved by the present invention is to provide an application of a urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material for preparing electrode active materials of supercapacitors and battery electrode materials.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a urea-formaldehyde resin-doped bamboo thin-wall cell porous carbon electrode material comprises the following steps:
[0007] 1) Carbonization: Mix and stir bamboo parenchyma cells and urea-formaldehyde resin powder, and press into tablets to obtain urea-formaldehyde resin-doped bamboo parenchyma cell composite materials; calcine the composite materials to obtain urea-formaldehyde resin-doped bamboo parenchyma cell charcoal;
[0008] 2) Activation: The carbonized sample is ground and mixed with an activator, calcined, taken out, cleaned to neutrality, and dried to obtain urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon.
[0009] In the step 1), the bamboo parenchyma cells are selected from moso bamboo.
[0010] In the step 1), the mass ratio of bamboo parenchyma cells to urea-formaldehyde resin is 1:1.
[0011] The calcination rate in steps 1) to 2) is 5°C / min.
[0012] The calcination temperature in step 1) is 500°C and the holding time is 2 h.
[0013] In the step 2), the mass ratio of the carbonized sample to the activating agent is 1:3.
[0014] In the step 2), the calcination temperature is 900°C and the holding time is 2 h.
[0015] The urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material is prepared by the preparation method of the urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material described in any one of the above items.
[0016] The urea-formaldehyde resin doped bamboo thin-wall cell porous carbon is used in preparing supercapacitor electrode active materials and battery electrode materials.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] (1) The present invention uses bamboo parenchyma cells and urea-formaldehyde resin as raw materials to prepare electrode materials. Bamboo parenchyma cells are easy to obtain and abundant as woody biomass, and their multi-walled cavity structure is conducive to activation and construction of pore structure; urea-formaldehyde resin expands when heated during pyrolysis, and a small amount is stored on the fiber surface, and more is stored in the cavity of the parenchyma cells. In the carbonization temperature range (<450 ° C), a large amount of CO2 and nitrogen-containing gas is released, which enriches the original pores of the carbonized material and realizes nitrogen doping. At the same time, after activation, the specific surface area of the porous carbon can be further increased. The production conditions of this method are simple and controllable, which is conducive to expanding production.
[0019] (2) The urea-formaldehyde resin-doped bamboo thin-walled cell porous carbon electrode material prepared by the present invention is applied to the positive electrode of zinc ion hybrid capacitors. It has high tap density and high mass specific capacity, and is a positive electrode material that is expected to be industrialized. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 SEM images of bamboo fiber, bamboo parenchyma cell and urea-formaldehyde resin composites after carbonization and activation, including: (a) bamboo fiber, (b) 500 ℃ bamboo fiber carbon, (c) 500 ℃ bamboo fiber-urea-formaldehyde resin carbon, (d) bamboo fiber-urea-formaldehyde resin activated carbon, (e) distribution of N element in bamboo fiber-urea-formaldehyde resin activated carbon, (f) bamboo parenchyma cell, (g) 500 ℃ bamboo parenchyma cell carbon, (h) 500 ℃ bamboo parenchyma cell-urea-formaldehyde resin carbon, (i) bamboo parenchyma cell-urea-formaldehyde resin activated carbon, (j) distribution of N element in bamboo parenchyma cell-urea-formaldehyde resin activated carbon;
[0021] Figure 2 This is the Raman spectrum of bamboo fiber, bamboo parenchyma cell and urea-formaldehyde resin composite material after activation;
[0022] Figure 3 This is the constant current charge and discharge curve of the prepared urea-formaldehyde resin doped bamboo parenchyma cell carbon. DETAILED DESCRIPTION
[0023] The present invention is further illustrated below in conjunction with specific examples. The examples are implemented based on the technical solutions of the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0024] The materials used in the following examples are 4-year-old bamboos collected from the International Bamboo and Rattan Center Anhui Taiping Experimental Center Forest Farm. The green and yellow parts of the bamboos were removed and then ground in a grinder and passed through a 40-60 mesh sieve. Bamboo powder with a 40-60 mesh sieve was placed in water and stirred for 5 minutes. The bamboo powder was separated into layers, the upper layer being bamboo thin-walled cells and the bottom layer being bamboo fibers. After being taken out, the powder was placed in an electric blower at 100°C and dried for 24 h to obtain bamboo thin-walled cells and bamboo fiber samples.
[0025] Example 1
[0026] Bamboo fiber (CF), bamboo parenchyma cell (PC) and urea-formaldehyde resin (UF) were placed in a burning boat respectively. The burning boat was placed in a tube furnace and heated to 500 ℃ at a heating rate of 5 ℃ / min. The boat was kept warm for 2 h under a nitrogen atmosphere. Then bamboo fiber charcoal (C-CF), bamboo parenchyma cell charcoal (C-PC) and urea-formaldehyde resin charcoal (C-UF) were obtained.
[0027] 2 g of bamboo fiber and 2 g of urea-formaldehyde resin powder were stirred in a beaker for 1 h, and the mixed powder was placed in a tableting mold and pressed into a 2×0.3 cm disc at a pressure of 12 MPa to obtain a urea-formaldehyde resin-doped bamboo fiber composite material. The composite material was placed in a calcining boat and calcined in a tube furnace. The temperature was raised to 500 ℃ at a heating rate of 5 ℃ / min and kept in a nitrogen atmosphere for 2 h. The urea-formaldehyde resin-doped bamboo fiber carbon (C-CF / UF) was obtained. In the same way and proportion, bamboo parenchyma cells and urea-formaldehyde resin were mixed and pressed into 2×0.3 cm discs, and then placed in a tube furnace for calcination to obtain urea-formaldehyde resin-doped bamboo parenchyma cell carbon (C-PC / UF).
[0028] Example 2
[0029] The carbonized sample of Example 1 was respectively ground and mixed with the activator KHCO3, the mass ratio of the carbonized sample to the activator being 1:3, and the mixture was heated to 900°C at a heating rate of 5°C / min in a tube furnace, and kept warm for 2 h under a nitrogen atmosphere. After the sample was taken out, it was thoroughly washed with 2 mol hydrochloric acid and water until the solution was neutral, and dried in an oven at 100°C for 12 h to obtain bamboo fiber porous carbon (A-CF), bamboo parenchyma cell porous carbon (A-PC), urea-formaldehyde resin porous carbon (A-UFR), urea-formaldehyde resin-doped bamboo fiber porous carbon (A-CF / UFR) and urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon (A-PC / UFR).
[0030] Example 3
[0031] Performance characterization:
[0032] Figure 1The SEM images of bamboo fiber, bamboo parenchyma cell and urea-formaldehyde resin composites after carbonization and activation. From Figures (a) and (f), it can be seen that the boundaries of fibers or parenchyma cells before carbonization and the multi-walled structure are obvious. From Figures (b) and (g), it can be seen that after carbonization at 500 ℃, the cell wall layers are fused, but the original structure of fibers and parenchyma cells is still retained. The fiber carbon shows the structural characteristics of thick wall and small cavity, the parenchyma cell carbon shows a cavity porous structure, and the urea-formaldehyde resin forms a flat cavity structure after carbonization. The fiber, parenchyma cell and urea-formaldehyde resin are carbonized. Since the urea-formaldehyde resin will first melt and then expand to release a large amount of gas during the pyrolysis process, it can be seen from Figure (c) that the urea-formaldehyde resin is coated on the fiber surface to form a macroporous structure, and a small amount enters the fiber cavity; the cavity structure of bamboo parenchyma cells provides space for the expansion of urea-formaldehyde resin. Figure (h) shows that the urea-formaldehyde resin fills most of the cavities of the parenchyma cells, which can significantly improve the tap density of the carbonized material. After activation, it can be seen from Figure (d) that the fiber still maintains its original structure, with a small amount of urea-formaldehyde resin residual carbon remaining on the surface; the thin-walled cell structure is destroyed, and the urea-formaldehyde resin and the thin-walled cell carbon structure are intertwined. It can be seen from Figure (i) that after activation, the surface of the urea-formaldehyde resin is severely etched to form a rich porous structure, which is conducive to achieving better electrochemical performance in supercapacitors.
[0033] Figure 2 This is the Raman spectrum of the porous carbon sample. It can be seen that at 1344 cm -1 and 1588 cm -1 There are two obvious characteristic peaks corresponding to sp 3 Hybridized carbon and ordered sp 2 Hybrid carbon, by comparing the degree of graphitization of porous carbon through the intensity ratio of ID / IG, it can be seen that the ID / IG ratio of bamboo fiber and bamboo thin-walled cells increased significantly after being compounded with urea-formaldehyde resin, indicating that nitrogen doping introduces more defects, which will form more chemical reaction sites on the surface of porous carbon materials, which is beneficial to improve the specific capacity of the material.
[0034] Figure 3 The constant current charge and discharge curve of the prepared urea-formaldehyde resin doped bamboo thin-walled cell carbon. It can be seen that the charge and discharge curve of the porous carbon sample is approximately an isosceles triangle, indicating a typical double-layer energy storage behavior. At a current density of 0.5A / g, the discharge time of A-PC / UFR is the longest, indicating better capacity performance.
[0035] Example 4
[0036] The preparation of zinc ion hybrid capacitor includes the following steps:
[0037] (1) The porous carbon electrode material prepared above was mixed with acetylene black and polyvinylidene fluoride binder in a mass ratio of 8:1:1, an appropriate amount of NMP was added, and the mixture was thoroughly stirred to form a slurry, which was then coated on carbon paper to serve as the positive electrode of the zinc ion hybrid capacitor;
[0038] (2) Preparing a 2 mol / L zinc sulfate aqueous solution as the electrolyte for the zinc ion hybrid capacitor;
[0039] (3) Assemble a zinc ion hybrid capacitor in the order of zinc metal negative electrode, cellulose separator (with zinc sulfate electrolyte added), and porous carbon electrode material positive electrode.
[0040] The comparison table of physical and chemical indexes of the carbon materials prepared in Example 1 and Example 2 is shown in Table 1 below:
[0041] Table 1 Comparison table of physical and chemical indicators of carbon materials
[0042]
[0043] As shown in Table 1, the specific surface area and pore structure of the thin-walled cells in the preparation method provided by the present application are 15.4% and 18.6% higher than those of the fibers. After compounding with urea-formaldehyde resin, the specific surface area of the composite porous carbon of fibers and thin-walled cells is as high as 1832 m 2 / g and 2162 m 2 / g, which increased by 35% and 38% respectively; the tap density of bamboo fiber carbon and thin-walled cell carbon were 0.555 g / cm 3 and 0.245 g / cm 3 After compounding with urea-formaldehyde resin, the tap density of fiber and thin-walled cell composite carbon increased to 0.663 g / cm 3 and 0.543 g / cm 3 , increased by 19.4% and 121.6%; after being assembled into a symmetrical supercapacitor, the mass specific capacity of urea-formaldehyde resin-doped bamboo thin-walled cell porous carbon was 33 F / cm 3 , increased by 21%, the specific capacity of urea-formaldehyde resin doped bamboo fiber porous carbon is 26 F / cm 3 , an increase of 18.9%.
[0044] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a urea-formaldehyde resin-doped bamboo thin-wall cell porous carbon electrode material, characterized in that: The following steps are involved: 1) Carbonization: Mix and stir bamboo parenchyma cells and urea-formaldehyde resin powder, and press into tablets to obtain urea-formaldehyde resin-doped bamboo parenchyma cell composite materials; calcine the composite materials to obtain urea-formaldehyde resin-doped bamboo parenchyma cell charcoal; 2) Activation: The carbonized sample is ground and mixed with an activator, calcined, taken out, cleaned to neutrality, and dried to obtain urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon.
2. The method for preparing the urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material according to claim 1, characterized in that: In the step 1), the bamboo parenchyma cells are selected from moso bamboo.
3. The method for preparing the urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material according to claim 1, characterized in that: In the step 1), the mass ratio of bamboo parenchyma cells to urea-formaldehyde resin is 1:
1.
4. The method for preparing the urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material according to claim 1, characterized in that: The calcination rate in steps 1) to 2) is 5°C / min.
5. The method for preparing the urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material according to claim 1, characterized in that: The calcination temperature in step 1) is 500°C and the holding time is 2 h.
6. The method for preparing the urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material according to claim 1, characterized in that: In the step 2), the mass ratio of the carbonized sample to the activating agent is 1:
3.
7. The method for preparing the urea-formaldehyde resin-doped bamboo thin-wall cell porous carbon electrode material according to claim 1, characterized in that: In the step 2), the calcination temperature is 900°C and the holding time is 2 h.
8. Urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material obtained by the preparation method of urea-formaldehyde resin-doped bamboo parenchyma cell porous carbon electrode material according to any one of claims 1 to 7.
9. Use of the urea-formaldehyde resin doped bamboo parenchyma cell porous carbon electrode material according to claim 8 in preparing supercapacitor electrode active materials and battery electrode materials.
Citation Information
Cited By
Biomass activated carbon and preparation method thereof, adsorbent and electro-adsorption device
CN118083971A